Estimation of Elastic Properties of Oil Palm Kernel Shell Concrete by Semianalytical Methods of Homogenisation - Mohamed Gibigaye; Fructueux Gildas Godonou; Crespin Prudence Yabi; Gerard Degan (Advances in Civil Engineering)
Despite its importance as one of the key parameters in the design of structural elements, the modulus of elasticity (MoE) is one of the least researched areas in oil palm kernel shell (OPKS) concrete. In the present study, we determined the MoE of OPKS concrete, using micromechanical models based on the classic approaches of homogenisation of Hashin–Shtrikman (HS) and Mori–Tanaka (MT). The MoE values for OPKSC (fcu < 35 MPa and OPKS volume fraction < 42%) estimated using the HS and MT models in the literature showed a good correlation with the experimental values. An empirical linear correlation between the volume fraction of inclusions and the MoE was proposed. The results obtained can enable better control of the mix design of structural concrete based on the proportion of OPKS coarse aggregate in tropical countries producing palm oil.